The First Case of 2019 Novel Coronavirus Pneumonia Imported into Korea from Wuhan, China: Implication for Infection Prevention and Control Measures - Kim, Jin Yong (J Korean Med Sci, 2020)
In December 2019, a viral pneumonia outbreak caused by a novel betacoronavirus, the 2019 novel coronavirus (2019-nCoV), began in Wuhan, China. We report the epidemiological and clinical features of the first patient with 2019-nCoV pneumonia imported into Korea from Wuhan. This report suggests that in the early phase of 2019-nCoV pneumonia, chest radiography would miss patients with pneumonia and highlights taking travel history is of paramount importance for early detection and isolation of 2019-nCoV cases.